Capital Structures in Developing Countries - Booth, Laurence; Aivazian, Varouj; Demirguc‐Kunt, Asli; Maksimovic, Vojislav (Journal of Finance, 2001)
ABSTRACT This study uses a new data set to assess whether capital structure theory is portable across countries with different institutional structures. We analyze capital structure choices of firms in 10 developing countries, and provide evidence that these decisions are affected by the same variables as in developed countries. However, there are persistent differences across countries, indicating that specific country factors are at work. Our findings suggest that although some of the insights from modern finance theory are portable across countries, much remains to be done to understand the impact of different institutional features on capital structure choices.